Horti-pasture for nutritional security and livelihood improvement in rainfed areas - Kumar, Sunil; Shukla, A.K.; Singh, H.V.; ., Satyapria (Indian Journal of Agroforestry, 2020)
Hortipastoral system is one of the best and economic alternative systems for rainfed area. It can supply the protective food (fruit) for human being and fodder for animal and thus help in bridging the wide gap between the supply and demand of fruit and fodder and secured nutrition and improved livelihood. A number of experiments on different fruitsÂ viz., Ber and Aonla, based hortipastoral systems on different aspects have been conducted in a phased manner since, last two decades (1990-2010). The production potential of system ranged as 7-15 t/ha fruit, 3-8 t/DM forage and 4-5 t/ha fuelwood from pruned biomass, besides soil improvement, preventing soil erosion. It resulted in higher Cost: Benefit ratio (1:3.7-6.24) and generates more employment (64.9 man days/year) opportunities than normal cropping system of rainfed farmers.